The stinging nettle as an alternative food crop - Dudás, László; Galambosi, Bertalan (Acta Agraria Debreceniensis, 2007)
Vegetables play an important role in human health and have an important effect on the human diet. It is equally serious to improve the volume, the diversity and the year round equability of vegetable consumption. The stinging nettle (Urtica dioica L.) is an alternative vegetable crop and available from the beginning of Spring to the end of Autumn; therefore, it can improve both the diversity and the equability of vegetable consumption. The stinging nettle has a superb nutritive value, it is a prospinach and it can be cooked in many ways.